Genotoxicity and Carcinogenicity Testing of Pharmaceuticals - Graziano, Michael J.; Jacobson-Kram, David (Springer International Publishing : Imprint: Springer, 2015)
This book provides an overview of the nonclinical testing strategies that are used to asses and de-risk the genotoxicity and carcinogenicity properties of human pharmaceuticals. It includes a review of relevant ICH guidelines, numerous case studies where follow-up studies were conducted to further investigate positive findings, and practical considerations for the use of alternative and emerging tests. With contributions from recognized experts in the pharmaceutical industry and health authorities, this volume presents a balanced view on the interpretation and application of genotoxicity and carcinogenicity regulatory guidances.   Genotoxicity and Carcinogenicity Testing of Pharmaceuticals is a valuable resource for scientists, regulators, and consultants that are engaged in the conduct, reporting, and review of nonclinical studies. This book will also help academicians better understand and appreciate the complexity of the regulations and breadth of toxicology research that are necessary to support the development and marketing of new drugs.